Polyhydroxyurethane hydrogels: Synthesis and characterizations. (November 2016) - Gennen, S.; Grignard, B.; Thomassin, J.-M.; Gilbert, B.; Vertruyen, B.; Jerome, C.; Detrembleur, C.
Graphical abstract: Highlights: Fast and quantitative coupling of CO2 with hydrophilic epoxides under mild conditions using organocatalysts. Synthesis of hydrophilic non-isocyanate polyurethane (NIPU) by solvent-free step-growth copolymerization. Preparation and characterization of novel NIPU hydrogels. Abstract: Hydrogels based on polyurethane (PU) are promising (bio-) materials because of their biocompatibility, biodegradation and excellent mechanical properties. In this publication, polyurethane hydrogels were produced for the first time by a non-isocyanate route by solvent-free step-growth copolymerization between a CO2 -sourced hydrophilic polyethylene glycol bi-cyclic carbonate with diamines in the presence of a cross-linker. Kinetic of poly(hydroxyurethane) (PHU) synthesis was monitored by ATR-IR and the chemical cross-linking was confirmed by rheology and gel contents measurements. Hydrogels were obtained by immersion of PHUs in water and the influence of the diamine/cross-linker ratio and the nature of diamine on the water swelling and compression properties (compression modulus, strain and stress at break) of PHU hydrogels was evaluated. Additionally, the compression properties of the hydrogels were improved by the addition of Montmorillonite as nanofiller in the PHU formulation. This work opens new application fields for CO2 -sourced PHUs.